Analisis Query MySQL pada Sistem Akademik - Nadia Syafitri; Afrio Irwando; Juma Riah (Prosiding SISFOTEK, 2025)
This study discusses the analysis of MySQL query optimization in academic information systems to improve database performance in supporting campus operational activities. The research scope includes identifying query performance issues in MySQL-based academic systems, applying various optimization techniques, and evaluating their impact on execution speed and resource efficiency. The main objective is to design effective and practical optimization strategies to reduce query response time and increase system throughput. The research employed an experimental quantitative method involving: (1) building a test environment that simulates a real academic system, (2) applying optimization techniques such as indexing, query rewriting, table partitioning, and MySQL parameter tuning, and (3) measuring performance using tools like EXPLAIN, mysqlslap, and sysbench. The dataset consisted of large synthetic data to represent real workloads. The results show that a combination of proper indexing, query rewriting based on execution plan analysis, and InnoDB parameter tuning significantly accelerates query execution time and reduces I/O load by more than 50% compared to the baseline configuration. The study concludes that applying appropriate MySQL query optimization techniques can significantly enhance academic system performance without requiring major architectural changes, providing practical guidance for developers and database administrators.